Revenue And Marketing Channel Of Oyster Mushroom In Probolinggo District - Lidyana, Novita; Perwitasari, Dyah Ayu; Rustianawati, Mutimmah (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
This research is a quantitative research. Primary data is the result of filling out questionnaires by all respondents, namely all mushroom farmers in Probolinggo. And secondary data in the form of all mushroom farmer data in Probolinggo with a total population of 60 mushroom farmers in Probolinggo. The selection of oyster mushroom farmer respondents was carried out using the census method. The samples in this study were all farmers who cultivated oyster mushrooms in Probolinggo Regency. The results of this study indicate that oyster mushroom farmers in Probolinggo use logs. By using this tool, it can increase the income of mushroom farmers. So that the oyster mushroom in Probolinggo is suitable to be used as a business / developed field. The marketing channel pattern of oyster mushrooms in Probolinggo uses two patterns. Namely the first pattern, mushroom farmers sell mushrooms to resellers, resellers will resell to retailers and retailers will sell again to end consumers. For the second pattern, mushroom farmers sell resellers, and resellers will sell directly to the final consumer. From the above analysis it can be concluded that the second channel is more profitable for farmers in terms of income.